2020
DOI: 10.1017/gmh.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation outcomes and strategies for depression interventions in low- and middle-income countries: a systematic review

Abstract: Background. We systematically reviewed implementation research targeting depression interventions in low-and middle-income countries (LMICs) to assess gaps in methodological coverage. Methods. PubMed, CINAHL, PsycINFO, and EMBASE were searched for evaluations of depression interventions in LMICs reporting at least one implementation outcome published through March 2019. Results. A total of 8714 studies were screened, 759 were assessed for eligibility, and 79 studies met inclusion criteria. Common implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 134 publications
1
28
0
Order By: Relevance
“…• Shortage of staff and required clinical skills • Only 15% of countries met all criteria for integrating mental health into primary care in 2020 83 • Insufficient perceived need 79,80,82,93 and population mental health literacy 92 • Stigma and discrimination, which reduce help-seeking 94 • Poor quality treatment [79][80][81][82] • Poor adherence with and negative attitude towards treatment 93,95 • Insufficient evidence about effective scale implementation of treatment [96][97][98] • Insufficient involvement of service users and families in treatment 83,99,100 and setting policy at local and government level 101…”
Section: Causes Of Mental Disorder Treatment Gapmentioning
confidence: 99%
“…• Shortage of staff and required clinical skills • Only 15% of countries met all criteria for integrating mental health into primary care in 2020 83 • Insufficient perceived need 79,80,82,93 and population mental health literacy 92 • Stigma and discrimination, which reduce help-seeking 94 • Poor quality treatment [79][80][81][82] • Poor adherence with and negative attitude towards treatment 93,95 • Insufficient evidence about effective scale implementation of treatment [96][97][98] • Insufficient involvement of service users and families in treatment 83,99,100 and setting policy at local and government level 101…”
Section: Causes Of Mental Disorder Treatment Gapmentioning
confidence: 99%
“…These challenges will require the continuous control and implementation of the corresponding reporting and analytical pathways ( 36 ). Thus, these analyses should be based on high-quality pragmatic designs and focus on later-stage implementation outcomes ( 37 ). A suggested way of reporting is the usage of validated indicators that describe referral processes and their cofactors ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used mixed-effects longitudinal regression analysis to examine the relationship between level of treatment exposure (measured as number of clinical visits) and magnitude of change in ZLDSI score from enrollment to endline, defined as the last date for which patients were recorded as receiving care. In the absence of a comparison group, this constitutes a longitudinal extension of pre-post treatment analysis that is common in the empirical literature (Adams et al ., 2015 ; Bernstein et al ., 2016 ; Wagenaar et al ., 2020 ). Due to the use of routinely collected data for this study and based on the observed efficacy of antidepressant and behavioral therapy, the research team deemed that a comparison group deprived of treatment would not be acceptable within the health system and would be considered to lack equipoise.…”
Section: Methodsmentioning
confidence: 99%